2017 IEEE 58th Annual Symposium on Foundations of Computer Science (FOCS) 2017
DOI: 10.1109/focs.2017.83
|View full text |Cite
|
Sign up to set email alerts
|

Testing Hereditary Properties of Ordered Graphs and Matrices

Abstract: We consider properties of edge-colored vertex-ordered graphs, i.e., graphs with a totally ordered vertex set and a finite set of possible edge colors. We show that any hereditary property of such graphs is strongly testable, i.e., testable with a constant number of queries. We also explain how the proof can be adapted to show that any hereditary property of 2-dimensional matrices over a finite alphabet (where row and column order is not ignored) is strongly testable. The first result generalizes the result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…The problem of understanding whether the statement of Theorem 1.3 holds for any finite family F of binary matrices, was raised in [5] and is still open. Only recently in [2] it was shown that the statement holds if we ignore the polynomial dependence, as stated in Theorem 1.1. Problem 1.4.…”
Section: Background and Main Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The problem of understanding whether the statement of Theorem 1.3 holds for any finite family F of binary matrices, was raised in [5] and is still open. Only recently in [2] it was shown that the statement holds if we ignore the polynomial dependence, as stated in Theorem 1.1. Problem 1.4.…”
Section: Background and Main Resultsmentioning
confidence: 91%
“…Here we do not try to optimize the dependence between the parameters, but rather to show that such a removal lemma exists. Note that in two dimensions this removal lemma follows from Theorem 1.1, but our results here suggest a direction to prove a weak high dimensional removal lemma without trying to generalize the heavy machinery used in [2] to the high dimensional setting. Our main result here states that this problem is equivalent in some sense to the problem of showing that if a hypermatrix M contains many pairwise-disjoint copies of a hypermatrix A, then it contains a "wide" copy of A; more details are given later.…”
Section: Multi-dimensional Matrices Over Arbitrary Alphabetsmentioning
confidence: 82%
See 3 more Smart Citations